Vehicle Multi-Pass Rut Volume and Mobility Power Study - William W Barbour (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
This paper presents the relationship between applied power by a wheeled vehicle to soil and the rutting effects. Specifically, a strong positive relationship was found between cumulative applied power and total rut volume across multiple passes by the vehicle over the same tracks. Field-testing was conducted using a high-mobility multi-purpose wheeled vehicle (HMMWV) and two distinct soil types. Sensors on the vehicle measured torque and angular velocity of each of the four wheels, from which applied power was calculated. A rut profile meter was used to document the shape of the rut after set numbers of passes and this profile was used to calculate rut volume. These results are useful for determining vehicle mobility power requirements based on soil rutting during multi-pass operation.
Keywords: rut; rutting; power; volume; traction; humvee; hmmwv; soil; engineering; tractor